2019
DOI: 10.1590/2177-6709.24.1.38.e1-7.onl
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 3D digital modeling of dental arches

Abstract: Objective: The aim of the study was to verify and compare the accuracy of full-arch digital impressions obtained using two intraoral scanners and three scanning methodologies. Methods: A resin model created with dental 3-D printing was scanned by a reference scanner (Zfx Evolution - Zimmer Biomet, Palm Beach Gardens, FL) in order to obtain a 3D reference; the same resin model was then scanned with two different intraoral scanners (Zfx IntraScan and Carestream 3600 - CS 3600®, Carestream, Rochester, NY, USA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
(31 reference statements)
1
13
0
2
Order By: Relevance
“…Moreover, the precision of the IOS was the lowest among the studied scanners, with a mean (SD) deviation of 0.23 (0.18) mm and a median (IQR) deviation of 0.18 (0.1–0.31) mm. This is also in line with literature reports; the authors of these reports still consider this an acceptable margin of deviation, and recommend the use of this scanner for clinical applications [ 17 , 19 , 24 , 25 , 34 , 35 , 36 , 37 , 38 ]. The higher deviations reported in our mandibular models are not in agreement with what was reported in the majority of the published studies, in which maxillary models showed higher deviations.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the precision of the IOS was the lowest among the studied scanners, with a mean (SD) deviation of 0.23 (0.18) mm and a median (IQR) deviation of 0.18 (0.1–0.31) mm. This is also in line with literature reports; the authors of these reports still consider this an acceptable margin of deviation, and recommend the use of this scanner for clinical applications [ 17 , 19 , 24 , 25 , 34 , 35 , 36 , 37 , 38 ]. The higher deviations reported in our mandibular models are not in agreement with what was reported in the majority of the published studies, in which maxillary models showed higher deviations.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, Lim et al reported a different range of deviation according to type of intraoral scanner, with the Trios showing greater precision (mean error, 52.3 μm) compared to iTero (60.5 μm) in 10 repeated patient oral cavity scans [23]. Some studies found that image errors seemed to result from various factors such as type of scanner, performer's experience, existence of crowding, and scanning technique [23][24][25][26]. In our study, the surface error range of repeated IOS images is similar to or slightly larger than those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[6,[14][15][16][17] Thus, direct intraoral scanning is an important tool for obtaining study models and analysis of dental measurements for children and young patients, since satisfaction with this method has already been shown to be higher in adults [18] and children. [10] However, more studies are still needed, especially clinical ones, since most studies in the literature analyze the accuracy of this method in resin models [13,17] so that it can be used in the same way as models obtained via conventional molding without harming future clinical conducts.…”
Section: Discussionmentioning
confidence: 99%